2006
DOI: 10.1021/nl061666f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Detection of Respiratory Virus Molecular Signatures Using a Silver Nanorod Array SERS Substrate

Abstract: A spectroscopic assay based on surface enhanced Raman scattering (SERS) using silver nanorod array substrates has been developed that allows for rapid detection of trace levels of viruses with a high degree of sensitivity and specificity. This novel SERS assay can detect spectral differences between viruses, viral strains, and viruses with gene deletions in biological media. The method provides rapid diagnostics for detection and characterization of viruses generating reproducible spectra without viral manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
446
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 593 publications
(453 citation statements)
references
References 33 publications
6
446
1
Order By: Relevance
“…is crucial in life sciences and medical diagnostics (1-5, 44, 45). Over the years, SERS has already proven to be a powerful platform to detect and analyze various biological entities such as proteins (46,47), viruses (48), and cells (49) as well as DNA (e.g., discriminate mutations) (50, 51) and RNA (11). As proof-ofconcept examples, we have shown that DNA bases of thymine and adenine as well as proteins such as bovine serum albumin (BSA) can be detected in water at subfemtomolar concentrations without additional labeling processes using SLIPSERS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…is crucial in life sciences and medical diagnostics (1-5, 44, 45). Over the years, SERS has already proven to be a powerful platform to detect and analyze various biological entities such as proteins (46,47), viruses (48), and cells (49) as well as DNA (e.g., discriminate mutations) (50, 51) and RNA (11). As proof-ofconcept examples, we have shown that DNA bases of thymine and adenine as well as proteins such as bovine serum albumin (BSA) can be detected in water at subfemtomolar concentrations without additional labeling processes using SLIPSERS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Silver nanoparticles are widely used in surface enhanced Raman scattering (SERS) spectroscopy (surface-sensitive technique which is known for its high sensitivity due to its surface plasmon effects lacks behind at uniform substrate formation) because of high local field enhancement factor. For example, it was demonstrated that SERS and silver nanorods quickly revealed the viral structures (Shanmukh et al 2006). It can also differentiate between respiratory viruses, virus strains, and viruses containing gene deletions without manipulating the virus.…”
Section: Applications Of Silver Nanoparticles and Their Incorporationmentioning
confidence: 99%
“…This novel SERS assay can detect spectral differences between viruses, viral strains and viruses with gene deletions in biological media. The method provides rapid detection and characterization of viruses generating reproducible spectra without viral manipulation (Shanmukh et al, 2006). Persistent infection with hepatitis B virus [HBV] is a major health problem worldwide and may lead to chronic hepatitis, cirrhosis and primary liver cancer (Ye et al, 2003).…”
Section: Avian Influenza Virus [Aiv]mentioning
confidence: 99%